2013
DOI: 10.2961/jlmn.2013.02.0003
|View full text |Cite
|
Sign up to set email alerts
|

Size Control of Gold Nanoparticles During Laser Ablation In Liquids With Different Functional Molecules

Abstract: Just as photolithography technology brought about the miniaturization of integrated circuits and drove multiple market opportunities in the electronics sector, a similar inflection point has arrived for ultrafast lasers. While these femtosecond class lasers have long enabled the precise manipulation of matter without heat affects, only recently, with the advent of commercial grade systems, has the potential of the technology been realized. Fiber optic architecture, embedded software control and robust telecom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Usually, solutions containing surfactants are used as protective agents to inhibit NP growth and stabilize NPs sterically or electrosterically . Surfactants with different sizes and carbon chains usually exhibit different performances in controlling the stability and size of synthesized products . Surfactants with longer hydrocarbon chains stabilize the NPs more efficiently, whereas those with shorter chains result in larger NPs .…”
Section: Material Process Liquid and Laser Parametersmentioning
confidence: 99%
“…Usually, solutions containing surfactants are used as protective agents to inhibit NP growth and stabilize NPs sterically or electrosterically . Surfactants with different sizes and carbon chains usually exhibit different performances in controlling the stability and size of synthesized products . Surfactants with longer hydrocarbon chains stabilize the NPs more efficiently, whereas those with shorter chains result in larger NPs .…”
Section: Material Process Liquid and Laser Parametersmentioning
confidence: 99%
“…Preferential avoidance of surfactants to generate “naked” NPs has driven the development of laser-assisted synthesis methods. One of the most popular techniques is pulsed laser ablation in liquid (PLAL), which involves irradiating a metal target immersed in solvent to generate plasma, vapor, and metal micro- or nanosized droplets, which can further react with the liquid medium to form NPs. , PLAL is emerging as a facile and versatile route to a variety of naked metal NPs, metal alloy NPs, and novel composite nanomaterials. In particular, PLAL is widely used to make naked AuNPs, and some degree of size control is achievable by modifying ablation geometry, changing the solvent, introducing salts, treating with successive laser fragmentation steps, , or adding surfactants. Despite the popularity of PLAL, proper AuNP size control without organic additives is still difficult, and products often exhibit high polydispersity. , …”
Section: Introductionmentioning
confidence: 99%
“…It was observed that in the case of laser ablation, the size of the nanoparticles depends upon the size of surfactant molecules, laser uence, and concentration of the surfactant. 133,134 Like the laser ablation method, the arc discharge method is also carried out in solution. 132 In this, an arc discharge is applied between gold metal electrodes in aqueous and anhydrous ethanol medium to prepare GNPs.…”
Section: Synthesis Of Gold Nanoparticlesmentioning
confidence: 99%